Salvage HIFU for biopsy confirmed local prostate cancer recurrence after radical prostatectomy and radiation therapy: Case report and literature review - Rittberg, Rebekah; Kroczak, Tadeusz; Fleshner, Neil; Drachenberg, Darrel (Canadian Urological Association Journal, 2015)
High-intensity focused ultrasound (HIFU) is a treatment option for low- and intermediate-risk prostate cancer and more recently has been used as salvage therapy after failed radiation therapy. We present a case of local recurrence with biochemical failure after radical prostatectomy and salvage external beam radiation therapy with salvage HIFU without biochemical recurrence at 20 months.